2020
DOI: 10.1007/s10995-020-02993-5
|View full text |Cite
|
Sign up to set email alerts
|

NM GRADS: Lessons Learned from Implementing a School-Based Program for Young Parents Across New Mexico

Abstract: Purpose The New Mexico Graduation Reality and Dual-role Skills (GRADS) program provides services for expectant and parenting students at high schools. The GRADS program has operated since 1989, serving more than 17,000 youth. This study summarizes the GRADS program model and program administrators’ lessons learned from implementing this comprehensive, large-scale program. Description The GRADS program is a multicomponent intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Moreover, to our knowledge, FRSIS presented a unique multi-agency model with an NGO working within schools and in close cooperation to bring about outcomes that will mostly be measurable in the long term. We acknowledge there are many Australian and international programs with the same general aims to promote education engagement and school completion to bolster long-term wellbeing and break cycles of disadvantage [ 36 37 38 39 40 41 42 43 ]. However, these programs tend to be limited to specific issues and/or family demographics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to our knowledge, FRSIS presented a unique multi-agency model with an NGO working within schools and in close cooperation to bring about outcomes that will mostly be measurable in the long term. We acknowledge there are many Australian and international programs with the same general aims to promote education engagement and school completion to bolster long-term wellbeing and break cycles of disadvantage [ 36 37 38 39 40 41 42 43 ]. However, these programs tend to be limited to specific issues and/or family demographics.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of mothers of premature children found that adolescent mothers had more depressive symptoms and less optimal caregiving compared to older parents [81 & ]. This, in turn, impacts the mental health of their children; children of adolescent mothers in this cohort had higher odds of developing symptoms of anxiety by age two [81 ].…”
Section: Parents Of Children With Medical Complexitymentioning
confidence: 92%
“…Adolescent parents can also receive supports through their schools. These supports can include individual classroom interventions, specific educational sessions, case management, and connections to health services and childcare [86 ▪ ,87 ▪ ]. One school-based program showed that adolescent parents had fewer unexcused absences, increased credits accumulated, and increased graduation rates after implementation of the program [86 ▪ ].…”
Section: Adolescent Parentsmentioning
confidence: 99%
“…Another concept in the discussion of decentralization is the concept of school-centeredness, which introduces the school itself as the main factor in improving the quality of education and indicates the need to increase the school's authority to produce curriculum content and self-fulfillment, motivation and sense of teacher progress based on this type is the curriculum (Nir, 2020). Decentralization means delegating more authority to schools and empowering staff to participate in decision-making and reducing the gap between principals and employees to achieve efficiency and effectiveness (Harper, Hopper, Keating & Harding, 2020). The move towards school-centered management is one of the most prominent developments in educational systems in the last two decades, and school-centered management is an effective strategy in decentralization and strategic guidelines and a plan to improve the education system by transferring authority and decision-making and empowering the school and its staff (Oecd, 2016).…”
Section: Introductionmentioning
confidence: 99%